The existence of law for the protection of society Adat Karuhun Urang (AKUR) Sunda Wiwitan - Suhendar, Suhendar; Agustin, Yullianti; Saefurrohman, Tommy; Sutrisno, Endang; Gunawan, Moch. Sigit (Edelweiss Applied Science and Technology, 2024)
Legal protection is fundamental in the concept of human rights. Because with legal protection, the fulfilment of other rights can only be realized optimally. Nevertheless, indigenous communities in Indonesia have yet to fully experience legal protection, as the state has not officially recognized their existence. This research addresses the legal framework for protecting the Sunda Wiwitan Indigenous Karuhun Urang (AKUR) community. The research employs a normative juridical approach, which relies on secondary data gathered through literature reviews. The goal is to examine whether there is legal recognition and protection for the AKUR community within existing regulatory frameworks. This research aims to find out legal protection of the recognition of the Sundanese Wiwitan Indigenous Karuhun Urang (AKUR) community and whether regulatory products concerning the existence of the Sundanese Wiwitan Indigenous Karuhun Urang (AKUR) community. From the above problems, it is concluded that the understanding of policymakers in formulating a model of protection and recognition of Indigenous Peoples is not yet comprehensive enough to answer the realities in the field and this is what makes policymakers unable to make a regulation related to the protection and recognition of indigenous peoples.